2021
DOI: 10.3390/s21051757
|View full text |Cite
|
Sign up to set email alerts
|

HARP: Hierarchical Attention Oriented Region-Based Processing for High-Performance Computation in Vision Sensor

Abstract: Cameras are widely adopted for high image quality with the rapid advancement of complementary metal-oxide-semiconductor (CMOS) image sensors while offloading vision applications’ computation to the cloud. It raises concern for time-critical applications such as autonomous driving, surveillance, and defense systems since moving pixels from the sensor’s focal plane are expensive. This paper presents a hardware architecture for smart cameras that understands the salient regions from an image frame and then perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In future work, we will apply region-based processing [4] to eliminate background information and obtain faster convergence for model training and inference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future work, we will apply region-based processing [4] to eliminate background information and obtain faster convergence for model training and inference.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is difficult to achieve good results with the scene classification task. Using the Sobel edge detection algorithm and Gaussian smoothing function to identify the relevant region in an image, Bhowmik et al [4] suggested region-based processing to discard background information and obtain a faster converge for deep learning model training. The image quality assessment method is used to quantify the level of image accuracy, which can be classified as subjective and objective methods.…”
Section: Introductionmentioning
confidence: 99%
“…In CNN, based on the original attention mechanism applied to the human visual system [31,32], the spatial attention mechanism was applied to it very early. For example, in the original picture information, focus on the area that needs more attention [33][34][35], and find the relationship weight of any pixel in the image to the current pixel from the global information [36]. In addition to spatial attention, many studies have focused on the attention mechanism of the convolution channel [37] in CNN.…”
Section: Related Workmentioning
confidence: 99%
“…In recent studies, the attention mechanism has been widely used in Convolutional Neural Network (CNN). From the spatial attention mechanism [31][32][33][34][35][36], channel attention mechanism [37], and part of the research used a mixed attention mechanism [38][39][40]. The attention mechanism itself calculates the features extracted by the model and adds more weight to the more important features of the result.…”
Section: Introductionmentioning
confidence: 99%
“…Image sensors (cameras) are an attractive choice because they provide a large amount of environmental information in pixels. This technology is constantly evolving [8,9] and, today, it is possible to have high-resolution cameras with high sampling rates [10][11][12]. Higher resolution cameras facilitate the detection task and allow the system to detect distant pedestrians, as they will be encoded in a greater number of pixels.…”
Section: Introductionmentioning
confidence: 99%